Regional determinants of Chinese inward foreign direct investment - LU, FEI (2013)
This study aims to examine the regional determinants of foreign direct investment (FDI) inflows among the eastern region, central region and western region of China. The sample of this study involves 31 provinces of China during the time period from 2003 to 2011. Panel data regression models are carried out to test what factors affect the locational choice of inward FDI and the differences among the three regions. Five potential regional determinants of FDI inflows are used in this paper, including the market size, labour cost, infrastructure, agglomeration and the degree of openness. Overall, the results show the agglomeration, the degree of openness and market size are the most significant factors of regional determinants of FDI inflows across China in recent years. While labour cost is found to have no significant impacts on the FDI inflows in central region and western region. Also we find the evidence to support that there exist differences of the effect of each potential determinant on deciding the FDI distribution in the three regions of China.